2020
DOI: 10.1093/mnras/staa815
|View full text |Cite
|
Sign up to set email alerts
|

The clustering of X-ray AGN at 0.5 < z < 4.5: host galaxies dictate dark matter halo mass

Abstract: We present evidence that AGN do not reside in "special" environments, but instead show large-scale clustering determined by the properties of their host galaxies. Our study is based on an angular cross-correlation analysis applied to X-ray selected AGN in the COSMOS and UDS fields, spanning redshifts from z ∼ 4.5 to z ∼ 0.5. Consistent with previous studies, we find that AGN at all epochs are on average hosted by galaxies in dark matter halos of 10 12 − 10 13 M ⊙ , intermediate between star-forming and passive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 97 publications
4
10
0
Order By: Relevance
“…Our model does not extend to ∼ 0, where the observational data are shown in dark blue. We note in particular the good agreement with the = 1.5 − 2.0 results (from Krishnan et al 2020 andPowell et al 2020, shown in purple in the right panel), which do show a substantial rise in the absolute bias from X ∼ 10 44 − 10 45 erg s −1 . Figure 8.…”
Section: Comparison To Observed Agn Clustering Measurementssupporting
confidence: 82%
See 1 more Smart Citation
“…Our model does not extend to ∼ 0, where the observational data are shown in dark blue. We note in particular the good agreement with the = 1.5 − 2.0 results (from Krishnan et al 2020 andPowell et al 2020, shown in purple in the right panel), which do show a substantial rise in the absolute bias from X ∼ 10 44 − 10 45 erg s −1 . Figure 8.…”
Section: Comparison To Observed Agn Clustering Measurementssupporting
confidence: 82%
“…Mendez et al (2016) found that matching on stellar mass alone was insufficient and that the SFR distribution of the galaxy population needed to be matched as well. Krishnan et al (2020) showed that matching the passive fraction of galaxy samples (i.e. the SFRs) was key to explain the clustering of AGN samples to ∼ 2.…”
Section: The Clustering Of Agn Relative To Galaxiesmentioning
confidence: 99%
“…In fact, this observation has been already recognised in the X-ray community (e.g. Leauthaud et al 2015;Mendez et al 2016;Powell et al 2018;Plionis et al 2018;Krishnan et al 2020). All these studies find no significant differences in the clustering properties of X-ray AGN compared to a matched galaxy sample.…”
Section: Qsos and The Dark Matter Halo Mass Functionsupporting
confidence: 57%
“…That is, X-ray AGN inhabit DM haloes that are consistent on average with the overall inactive galaxy population. This result runs from the local Universe (0.01 < z < 0.1; Powell et al 2018) to high redshifts, z 4.5 (Krishnan et al 2020). Studying narrow-line AGN, and comparing to a matched control samples of inactive galaxies, Li et al (2006) find that AGN have almost the same clustering amplitude as the control galaxies, on scales larger than a few Mpc.…”
Section: Qsos and The Dark Matter Halo Mass Functionmentioning
confidence: 89%
See 1 more Smart Citation